An audit of the laboratory diagnosis of cryptosporidiosis in England and Wales. Issue 7 (July 2015) - Chalmers, Rachel M.; Atchison, Christina; Barlow, Katrina; Young, Yvonne; Roche, Anita; Manuel, Rohini
Abstract : N/A: To assess the level of practice consistent with UK national standards for Cryptosporidium testing, an audit was performed of 156 publicly funded clinical microbiology laboratories in England and Wales between August 2013 and April 2014. Responses were received from 85 (54 %) laboratories. First line diagnostic methods used were mainly microscopy with modified Ziehl–Neelsen (mZN) or auramine phenol (AP) staining (68/85, 80 %), enzyme immunoassays (EIAs) (16/85, 19 %) or in‐house PCR (1/85, 1 %). The use of EIAs was more widespread than reported previously. Various methods were used for confirmation of positive EIA reactions and laboratories frequently resorted to sending samples to the national reference laboratory for this purpose, indicating that guidance is required for performance monitoring and confirmation of positive reactions. Laboratory positivity rates were related to the diagnostic test used, with highest median rates reported by those using PCR, EIAs or AP microscopy, and the lowest by those using mZN microscopy. One‐third of responding laboratories (28/85, 33 %) routinely tested all stools for Cryptosporidium . However, 16 (19 %) laboratories used stool consistency to decide whether to test for this parasite. Other selection criteria included patient age ( n = 18; 21 % laboratories), history or clinical details ( n = 40; 47 %), duration of hospitalization ( n = 18; 21 %) or clinician requests ( n = 25; 29 %). To encourage laboratories to test all stools submitted for the investigation of diarrhoeal illness for Cryptosporidium, revision of the guidance in the national standards is under way. This will enable improved assessment of the burden of illness and ability to monitor outbreaks, and measure changes in reported cases.